Jews and muslims in Europe: between discourse and experience - Everett, Samuel Sami; Gidley, Ben (Annual review of the sociology of religion, 2022)
This Annual Review of the Sociology of Religion contributes cases of encounters, diversities and distances to an emerging Jewish-Muslim Studies field. The scholarly essays address both discourses about and lived experiences of minorities in contemporary French, German and UK cities. The authors explore how particular modes of governance and secularism shape individual and collective identities while new technologies re-make interfaith encounters. This volume shows that Middle Eastern and North African pasts and presents weigh on European realities, examines how the pull of Jewish intellectual history is felt by a new generation of Muslim scholars and activists, and uncovers how Orthodox communities negotiate living side by side